Dancing: Creative, healthy teen activity. Issue 1 (1st January 2014) - Gill, Sam
Focused on the Cuban social salsa dance rueda de casino, which has been especially developed for teens, Sam Gill argues that dancing is an exemplar of the most important activities that teenagers can do to nourish their development and to assure that they will achieve their potential. Gill demonstrates this claim in some detail from a variety of perspectives, including motivation and happiness, touch and contact, movement and the kinaesthetic sense, physical exercise, community and diversity, creativity and individuality, gender, music, and his own theoretical construct self-othering. Gill argues that while teens need to engage in many kinds of experience, and need to learn language arts, history, mathematics, social sciences, natural sciences, and so much more, dancing is one of the fundamental experiences that make our humanness possible.